Grazing Practices and Pasture Tenure in the Eastern Pamirs The Nexus of Pasture Use, Pasture Potential, and Property Rights - Vanselow, Kim; Kraudzun, Tobias; Samimi, Cyrus (Mountain Research and Development, 2012)
This paper deals with the relations between grazing practices, pasture potential, and property rights in the Eastern Pamirs of Tajikistan 10 years after the privatization of 1999. It provides an overview of the spatiotemporal variability of current pasture use and livestock numbers. Assumptions about pasture potential are reconsidered in relation to animals' forage needs in order to draw field-based conclusions regarding over-or underuse in particular areas. Data are derived from interdisciplinary research on post-Soviet pastoralism and associated human-environment interactions. We show that pastoralists in the Eastern Pamirs face several problems: As the land cover resources are meager and variable and hay meadows for winter fodder are rare, herd mobility or external forage inputs are necessary to compensate for weather-related shortages. The current multiseasonal pasture use-a change from the mono-seasonal use of Soviet state farms-discourages plant regeneration. Competition between pastoralist groups is exacerbated by unresolved questions about formal user rights. Conflicts seem inevitable, limiting the sustainable use of natural resources. Based on 2 telling examples, we show that pastures close to villages are used year round, particularly in winter, and are heavily overgrazed. There is less grazing pressure on summer pastures, but some distant and hardly accessible summer pastures show high livestock numbers in summer, contradicting former opinions about their underuse.
Keywords: Pasture use; pasture potential; pasture tenure; carrying capacity; grazing pressure; transformation processes; Pamirs; Tajikistan